2020
DOI: 10.2174/1573404816666200310125636
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Quality of Life Style and Risk of Infertility: A Systematic Review Study

Abstract: Background: Infertility and its mental, social, and economic issues endanger the couples' lives. Adverse quality of life style is a threat to the reproductive health and can lead to infertility problems Objective: The present systematic review study was conducted to investigate the impact of adverse quality of lifestyle on increased risks of infertility. Method: After selecting electronic databases, namely Scopus, Pub Med, SID, and Web of Science, we searched the total population of available and publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Findings in Italian fertile women showed an inverse relationship between obesity and LH and FSH levels. In the present in this research, a positive relation was found between FSH and obesity (41) . In addition, infertility risk rises when there is an imbalance between oxidants and antioxidants, which can be caused by hormonal fluctuations.…”
Section: Lh Concentration In Tablesupporting
confidence: 65%
“…Findings in Italian fertile women showed an inverse relationship between obesity and LH and FSH levels. In the present in this research, a positive relation was found between FSH and obesity (41) . In addition, infertility risk rises when there is an imbalance between oxidants and antioxidants, which can be caused by hormonal fluctuations.…”
Section: Lh Concentration In Tablesupporting
confidence: 65%
“…[ 2 ] The most important causes of male infertility include congenital or acquired abnormalities of the genitourinary system. [ 3 ] The presence of the malefactor is often based on abnormal sperm parameters. [ 4 ] Impaired sperm production and function and damage to the spermatogenesis process are among the most common causes of male infertility.…”
Section: Introductionmentioning
confidence: 99%